Earthquake and Physical and Social Vulnerability Assessment for Settlements: Case Study Avcilar District - Yucel, Gul; Arun, Gorun (YILDIZ TECHNICAL UNIV, FAC ARCHITECTURE, 2010)
Many settled areas in Turkey and across the globe suffer economical and social losses resulting from natural disasters such as earthquakes, floods, hurricanes and landslides. In this study, a vulnerability assessment model has been developed for earthquake prone areas in Turkey. The vulnerability assessment model includes ground factors, a building's physical conditions, building evacuation and social (demographic and socioeconomic) aspects of the settlement. The ground vulnerability factor is calculated using factors such as the earthquake zone, soil classification, land sliding and liquefaction threats. The physical vulnerability factor depends on the structural and non- structural threats of the building; the building evacuation vulnerability factor includes the position and structural system of the staircase, the width and natural illumination of the evacuation route, the size and opening of the building exit doors to the street and the distance of the building to the closest open area. The social vulnerability factor considers the age group, gender, family type, education, ownership, income etc of the building users. This vulnerability assessment model is applied to a case study - that of the Avcilar district of Istanbul. Forty different reinforced concrete residential buildings (349 apartments) of 1225 people are assessed using the develop checklist. In order to evaluate the checklist and to assess the importance (relevance) of vulnerability factors, a questionnaire is forwarded to various related professional groups (architecture, urban planning and civil engineering). The results of the questionnaire are examined using SPSS software with factor analysis. According to the results, most of the samples in the case study area can be classified as high vulnerable.
Keywords: Earthquake; physical vulnerability; social vulnerability; evacuation route; evacuation area; Architecture